'Love with Less Salt': evaluation of a sodium reduction mass media campaign in China. Issue 10 (12th October 2022) - Gupta, Ashish K; Carroll, Tom E; Chen, Yu; Liang, Wenzhuo; Cobb, Laura K; Wang, Yichao; Zhang, Juan; Chen, Yeji; Guo, Xiaolei; Mullin, Sandra; Murukutla, Nandita
Abstract : Objective: This study examines the impact of a salt reduction campaign on knowledge, attitudes, intentions, behaviours and barriers to behaviour change relating to salt consumption in two provinces of China. Methods: In 2019, the 'Love with Less Salt' campaign ran on China Central Television and on local television channels in Shandong and Anhui provinces. Data for this study come from two representative household surveys conducted among a sample of adults aged 25–65 years in Shandong and Anhui provinces: precampaign (n=2000) and postcampaign (n=2015). Logistic regression was performed to estimate the effects of the campaign on knowledge, attitudes, intentions, behaviours and barriers to behaviour change. Results: Overall, 13% of postcampaign respondents recalled seeing the campaign, and reactions towards the campaign were positive. Postcampaign respondents were more likely to plan to reduce their purchase of foods high in salt than precampaign respondents (OR=1.45, p=<0.05). Campaign-aware respondents were significantly more likely than campaign-unaware respondents to report higher levels of knowledge, attitudes and behaviours regarding salt reduction. Conclusions: Findings reveal that salt reduction mass media campaigns can be an effective public health tool to support efforts to reduce salt consumption in China. Continued and sustained mass media investments are likely to be effective in addressing high salt consumption nationwide.